Identification of novel long non-coding RNAs involved in bisphenol A induced immunotoxicity in fish primary macrophages. Issue 100 (May 2020) - Liu, Shuai; Pan, Chenyuan; Tang, Yi; Chen, Fangyi; Yang, Ming; Wang, Ke-Jian
Abstract: Bisphenol A (BPA), a well-known environmental endocrine-disrupting chemical (EDC), could pose a great toxicity risk to aquatic organisms. The present study aimed to evaluate the underlying role of long non-coding RNAs (lncRNAs) in BPA-induced immunotoxicity in head kidney (HK) macrophages of the red common carp ( Cyprinus carpio ), using lncRNA-RNA sequencing (RNA-Seq). In BPA-exposed HK macrophages group, 2, 095 and 1, 138 differentially expressed mRNAs (DEGs) and lncRNAs (DE-lncRNAs) were obtained, respectively, compared with controls. The qRT-PCR validation results of DEGs and DE-lncRNAs were similar to the RNA-Seq results. The KEGG analysis of DEGs and target genes of DE-lncRNAs have shown that some immune-related signaling pathways, including NF-kappa B, Toll-like receptor, B-cell receptor, Jak-STAT, and Hippo signaling pathways, were severely disrupted by BPA exposure. Moreover, we observed the synergic regulation of some mRNAs involved in immune response such as two hub genes traf6 and mapk1/3 and their upstream lncRNAs in HK macrophages upon the BPA exposure or its analogue bisphenol S (BPS) exposure. This suggested the dysregulation of lncRNAs by BPA or BPS may lead to a change in the expression of hub genes, which affects the cross-talk of various signaling pathways by interaction with other network genes. In conclusion, the present study demonstrates the potential role of lncRNAs in immunotoxicity of bisphenol compounds in red common carp HK macrophages, and our results provide evidence for further exploring lncRNA's role in EDC-induced toxicity in aquatic organisms. Highlights: BPA can induce an immune response in head kidney macrophages from red common carp. Multiple signaling pathways (NF-κB, TLR, BCR, Jak-STAT, and Hippo) were involved. Novel BPA specific lncRNAs were identified and their target genes were predicted. BPA and BPS both changed selected immune-related mRNAs and their upstream lncRNAs. This study provide evidence for lncRNA's role in bisphenol induced immunotoxicity.